Conception of Franchise Agreement in Protecting the Legal Interests of Parties Based on Indonesian Civil Law - Masitah Pohan (International Journal Reglement & Society (IJRS), 2020)
Franchising is an effective way to expand business networks and respond to modern challenges, because the system does not require direct investment, but involves cooperation with other parties. In other words, franchising is a form of partnership based on a mutually beneficial relationship (mutualistic symbiosis) between the franchisor and the franchisee. The success or failure of a business with a franchise system depends entirely on the ability of the franchisee business partner to develop and run the franchise business through the procedures, processes and rules set by the franchisor. In the franchise system, the franchisee is given the right to take advantage of the intellectual property rights and the operating system of the franchisor, whether the use of trademarks, service marks, copyrights on logos, industrial designs, patents or trade secrets. This research is a type of normative legal research. Normative legal research is research whose data comes from secondary data and since this research data is secondary data, it is included in the type of normative legal research. This type of research used in this writing is library research. Library research means research using written documents as data, and data sources used in this study include primary legal materials and secondary legal materials. Based on the research results, it is known that the provisions of Article 1338 of the Civil Code confirm that all agreements made legally are valid as laws for those who make them. An agreement cannot be withdrawn as long as both parties agree or for reasons that are stated by law to be sufficient for that. An agreement must be carried out in good faith. On the basis of the provisions contained in Article 1338 of the Civil Code, it will be known the principles of freedom of contract, namely that every person is free to enter into an agreement or is free to determine the contents of an agreement as long as it does not contradict the law and public order.